2021
DOI: 10.3390/s21238162
|View full text |Cite
|
Sign up to set email alerts
|

Individual Tree Structural Parameter Extraction and Volume Table Creation Based on Near-Field LiDAR Data: A Case Study in a Subtropical Planted Forest

Abstract: Individual tree structural parameters are vital for precision silviculture in planted forests. This study used near-field LiDAR (light detection and ranging) data (i.e., unmanned aerial vehicle laser scanning (ULS) and ground backpack laser scanning (BLS)) to extract individual tree structural parameters and fit volume models in subtropical planted forests in southeastern China. To do this, firstly, the tree height was acquired from ULS data and the diameter at breast height (DBH) was acquired from BLS data by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Kukko et al [20] employed MLS and GNSS/INS technologies, using graph optimization to refine data trajectories, thus efficiently mapping forests, and determining tree parameters. Gao et al [21] leveraged near-field LiDAR data from UAV and ground backpack scanners to determine the structural parameters of trees in subtropical planted forests. The findings affirm near-field LiDAR's effectiveness in extracting tree structural details.…”
Section: Literature Review On the State Of The Art In Forest Operationsmentioning
confidence: 99%
“…Kukko et al [20] employed MLS and GNSS/INS technologies, using graph optimization to refine data trajectories, thus efficiently mapping forests, and determining tree parameters. Gao et al [21] leveraged near-field LiDAR data from UAV and ground backpack scanners to determine the structural parameters of trees in subtropical planted forests. The findings affirm near-field LiDAR's effectiveness in extracting tree structural details.…”
Section: Literature Review On the State Of The Art In Forest Operationsmentioning
confidence: 99%
“…Jayathunga et al [ 55 ] estimated the standard deviation of height, percentile height, coefficient of variation in height, skewness, and kurtosis, and canopy cover above mean height using Fixed-Wing UAV. Gao et al [ 56 ] combined UAV laser scanning and ground backpack laser sacking to extract individual tree structural parameters and fit volume models in subtropical planted forests in southeastern China.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The complex nature of natural stands makes single tree detection in point clouds challenging; utilizing a simpler canopy detection method that does not explicitly attempt to distinguish overlapping canopies may be an alternative solution for tree segmentation in these types of environments. An example of such a method that has been successful in mature mixedwood forests is the distance judgment clustering approach [68,69]. This method assumes that the distance between trees is greater at their apex compared to the ground and uses those distances to cluster and segment trees.…”
Section: Tree Heightmentioning
confidence: 99%
“…One of the benefits of MLS relative to RPAS LiDAR is the increased point cloud density in the lower canopy which facilitates DBH measurements [39,69]. A number of studies have observed acceptable ranges of DBH accuracy when sampling trees in both planted and natural stands; however, the general consensus is that accuracy is highest for trees with DBHs between 10 and 20 cm [40,66,73].…”
Section: Tree Dbhmentioning
confidence: 99%